SIFAT FISIS DAN MEKANIS BATANG KELAPA (Cocos nucifera L.) DARI KALIMANTAN SELATAN - Dwi Harsono (Kementerian Perindustrian, 2011)
The aim to of this research is to know characters physical and mechanical characteristics of coconut wood based on 3 growth places (highland, coast and swamps) and the position of the coconut wood (tip, middle, and base). Besides that, to support the growth and the spreading of wood processing industry in South Borneo. They are two treatment factors that are used, the variation of growth places (highland, coast and swamps) and the variation of wood position (tip, middle, and base). Every combination of the treatments are repeated three times. The best Physical and mechanical characteristics of coconut wood is from highland and in the base part of the wood. The coconut wood can be used for structural wood.Keywords: coconut wood, physical characteristics, mechanic characteristics